Sex Differences in Age and Comorbidities for COVID-19 Mortality in Urban New York City - Klang, Eyal (SN Compr Clin Med, 2020)
Previous studies demonstrated a higher COVID-19 fatality rate in men. The aim of this study was to compare age and comorbidities between women and men who died from COVID-19. We retrospectively analyzed data of COVID-19 patients hospitalized to a large academic hospital system in New York City between March 1 and May 9, 2020. We used a multivariable logistic regression model to identify independently significant variables associated with gender in patients who died from COVID-19. The model was adjusted for age and comorbidities known to be associated with COVID-19 mortality. We identified 6760 patients diagnosed with COVID-19. Of these patients, 3018/6760 (44.6%) were women. The mortality rate was higher for men (women 18.2% vs. men 20.6%, p = 0.039). Of the patients who died, women were on average 5 years older than men (woman 77.4 ± 12.7 vs. men 72.4 ± 13.0, p < 0.001). In the multivariable model, cardiovascular comorbidities were not significantly different between women and men. Chronic kidney disease (aOR for women 0.7, 95% CI 0.5–0.9) and smoking (aOR for women 0.7, 95% CI 0.5–0.9) were more common in men. Age decile (aOR for women 1.4, 95% CI 1.3–1.6) and obesity (aOR for women 2.3, 95% CI 1.8–3.0) were higher in women. This study demonstrates that women who died of COVID-19 showed a similar cardiovascular disease profile as men. Yet, they are 5 years older than men. Investigating the gender impacts of COVID-19 is an important part of understanding the disease behavior.